2013
DOI: 10.1016/j.jneb.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a School-based Internet Obesity Prevention Program for Adolescents

Abstract: Objective To evaluate the reach, adoption, and implementation of HEALTH[e]TEEN, a school-based Internet obesity prevention program, and examine differences in student participation and satisfaction by school, gender, age, and race/ethnicity. Design Mixed methods, clinical trial of HEALTH[e]TEEN. Setting 3 Public high schools in Connecticut. Participants 384 adolescents, 8 teachers. Intervention(s) HEALTH[e]TEEN vs. HEALTH[e]TEEN + coping skills training. Main Outcome Measure(s) Demographic and state-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 49 publications
0
38
0
2
Order By: Relevance
“…45 Teens endorsed the proposed peer education model which inherently involves building a social support network to promote healthier behaviors, peer role modeling, and opportunities to learn through vicarious experiences. Teens also suggested that support may extend beyond the inperson sessions using strategies such as group text messages, 46,47 interactive websites, 48,49 and communication through online or mobile social networks.…”
Section: Discussionmentioning
confidence: 99%
“…45 Teens endorsed the proposed peer education model which inherently involves building a social support network to promote healthier behaviors, peer role modeling, and opportunities to learn through vicarious experiences. Teens also suggested that support may extend beyond the inperson sessions using strategies such as group text messages, 46,47 interactive websites, 48,49 and communication through online or mobile social networks.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study methods, design, implementation, and the primary study results have been described in greater detail elsewhere (Whitte-more, Jeon, & Grey, 2013; Whitte-more, Chao et al, 2013). In brief, a convenience sample of adolescents between the ages of 14 and 17 years (Grades 9 to 11) was recruited from classrooms in three high schools in or near New Haven, Connecticut, between October 2010 and January 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was diverse with approximately 64% of participants from minority backgrounds, and within each school, the percentage of minority students who enrolled in the study was equivalent to or greater than the overall school demographic characteristics (Whittemore, Chao et al, 2013). Nurses and teachers in the schools in which the HEALTH[e]TEEN program was implemented were supportive of the program (Whittemore, Chao et al, 2013); however, their role in health education was primarily provided during individual and specific encounters with students, not as a component of structured obesity prevention health classes. Indeed, two of the three schools required physical education classes for at least 1 year, which also included some health content on nutrition and PA. All students in the sample had access to a school nurse, but the role of the school nurse varied per institution from full-time to part-time to a school-based health clinic.…”
Section: Methodsmentioning
confidence: 99%
“…Implementation and effective outreach are often dependent not only on motivational factors but also on teachers' acceptance of the program and the school environment in general. It has also been found that print-based programs remain almost equally as effective as internet-based programs [17].…”
Section: E-health Prevention At the Meso Level: Education And The Heamentioning
confidence: 99%